BUKU PANDUAN PERMAINAN DAM QUIZ SEBAGAI MEDIA UNTUK MELATIH KETERBUKAAN DIRI - Sania Putri Salsabila; Guruh Sukma Hanggara; Vivi Ratnawati; Laelatul Arofah (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2023)
The rationale for this research is to increase the openness of high school students so that students can adapt to their school environment. This study aims to (1) describe the procedure for developing a guidebook, (2) determine the validity of developing a guidebook, (3) determine the effectiveness of developing a guidebook for the game Dam Quiz as a medium for practicing self-disclosure. This study uses the ADDIE model according to Hasyim (2016) which consists of 5 stages, namely ADDIE (Analysis, Design, Development, Implementation, Evaluation), but this research implements the ADDIE model only in 3 stages, namely analysis, design and development. This research was conducted at Al-Huda Islamic Middle School with counseling teachers and students using guidebooks.